A new species of Catinia Bocquet & Stock, 1957 (Copepoda, Catiniidae) associated with mud shrimps, Axianassa australis Rodrigues & Shimizu, 1992 (Decapoda, Thalassinidea, Laomediidae), from Brazil - Kihara, Terue C.; Rocha, Carlos E.f.; Santos, Cynthia (Zootaxa, 2005)
Catinia aiso sp. n. was found in association with the mud shrimp, Axianassa australis Rodrigues & Shimizu, 1992 collected in the intertidal zone of Araçá Beach, state of São Paulo, Brazil (23°48’50’’S, 45°23’48’’W). The new species shares with Catinia plana Bocquet & Stock, 1957 the structure of the oral appendages, the setal formula of the swimming legs, the robust pedunculate sucker on the antenna, and the absence of the maxilliped in adult females. However, the two species can be separated by the rostrum shape, the presence or absence of an inner coxal seta on leg 4, and the structure of leg 5 in both sexes. Catinia aiso also differs from C. plana in the depressed ovoid body shape, the ornamentation of the maxilla in the female and in the modified claw of the maxilliped of the male. The sexual dimorphism expressed in the armature of the antennule and the endopodal segments of the swimming legs in C. plana, is absent in C. aiso. This is the first record of Catinia since the genus was established on the basis of material from the Baie de Morgat, France, in 1957.